Molecular Characterization and Clinical Relevance of RNA Binding Proteins in Colorectal Cancer - Zhang, Zhen; Wang, Ling; Wang, Quan; Zhang, Mengmeng; Wang, Bo; Jiang, Kewei; Ye, Yingjiang; Wang, Shan; Shen, Zhanlong (Frontiers in Genetics, 2020)
Abnormal expression of RNA Binding Proteins (RBPs) have been reported across various cancers. However, the potential role of RBPs in colorectal cancer (CRC) remains unclear. In this study, we performed a systematic bioinformatics analysis of RBPs in CRC. We downloaded CRC data from the Cancer Genome Atlas (TCGA) database. Our analysis identified 242 differentially expressed RBPs between tumor and normal tissues, including 200 upregulated and 42 downregulated RBPs. Next, we found that eight RBPs (RRS1, PABPC1L, TERT, SMAD6, UPF3B, RP9, NOL3, PTRH1) were related to the prognoses of CRC patients. Among these eight prognosis-related RBPs, four RBPs (NOL3, PTRH1, UPF3B and SMAD6) were selected to construct a prognostic risk score model. And our results indicated that the prognostic risk score model accurately predicted prognosis of CRC patients (AUC for 3- and 5- year OS was 0.645 and 0.672, respectively). Furthermore, we developed a nomogram based on a prognostic risk score model. The nomogram was able to demonstrate the wonderful performance in predicting 3- and 5-year OS. Additionally, we validated the clinical value of four risk genes in the prognostic risk score model and identified that these risk genes were associated with tumorigenesis, lymph node metastasis, distant metastasis, clinical stage and prognosis. Finally, we used the TIMER and HPA database to validate expression of four risk genes at the transcriptional and translational level, respectively, and used a clinical cohort to validate the roles of NOL3 and UPF3B in predicting the prognosis of CRC patients. In summary, our study demonstrated that RBPs have an effect on CRC tumor progression and might be potential prognostic biomarkers for CRC patients.